Pelatihan Seni Grafis Cetak Datar Berbasis Kearifan Lokal Banyuwangi untuk Meningkatkan Kreativitas dan Karakter Siswa MIN 3 Banyuwangi - Erisy Syawiril Ammah; Sudarsri Lestari; Atiqatul Musyarofah; Nur Hermatasiyah (Education and Community Service Journal (EduServe), 2026)
Strengthening local wisdom through primary education is a strategic effort to foster students’ character while preserving regional culture. However, art learning activities in schools are still largely limited to simple practices and have not provided sufficient opportunities for students to engage in hands-on experiences that integrate creativity, practical skills, and an understanding of local culture. One of the challenges faced by MIN 3 Banyuwangi is the lack of project-based activities that can simultaneously enhance students’ creativity and introduce Banyuwangi’s local wisdom in a practical and meaningful way. This community service program aimed to improve students’ creativity, collaborative skills, and understanding of local culture through flat printmaking training based on Banyuwangi local wisdom. The program was conducted in February 2026 and involved 87 fifth-grade students of MIN 3 Banyuwangi. The implementation stages included needs assessment, socialization, group formation, practical printmaking activities using wooden cutting boards as the printing medium, an art exhibition, and program evaluation through participatory observation. The results showed that all student groups successfully produced printmaking artworks inspired by Banyuwangi cultural themes, including Gajah Oling batik motifs, Gandrung and Seblang traditional performances, and other local cultural icons. In addition to enhancing students’ creativity and fine motor skills, the program also strengthened their collaboration, self confidence, and appreciation of local culture. The exhibition held at the end of the program provided students with basic entrepreneurial experience and fostered the values embodied in the Pancasila Student Profile. Therefore, local wisdom-based flat printmaking training can serve as an alternative program for character development and the preservation of local culture within the madrasah environment.